Economics of Alaska North Slope gas utilization options - Thomas, C. P.; Doughty, T. C.; Hackworth, J. H.; North, W. B.; Robertson, E. P. (Lockheed Martin Idaho Technologies Co., Idaho Falls, ID (United States), 1996)
The recoverable natural gas available for sale in the developed and known undeveloped fields on the Alaskan North Slope (ANS) total about 26 trillion cubic feet (TCF), including 22 TCF in the Prudhoe Bay Unit (PBU) and 3 TCF in the undeveloped Point Thomson Unit (PTU). No significant commercial use has been made of this large natural gas resource because there are no facilities in place to transport this gas to current markets. To date the economics have not been favorable to support development of a gas transportation system. However, with the declining trend in ANS oil production, interest in development of this huge gas resource is rising, making it important for the U.S. Department of Energy, industry, and the State of Alaska to evaluate and assess the options for development of this vast gas resource. The purpose of this study was to assess whether gas-to-liquids (GTL) conversion technology would be an economic alternative for the development and sale of the large, remote, and currently unmarketable ANS natural gas resource, and to compare the long term economic impact of a GTL conversion option to that of the more frequently discussed natural gas pipeline/liquefied natural gas (LNG) option. The major components of the study are: an assessment of the ANS oil and gas resources; an analysis of conversion and transportation options; a review of natural gas, LNG, and selected oil product markets; and an economic analysis of the LNG and GTL gas sales options based on publicly available input needed for assumptions of the economic variables. Uncertainties in assumptions are evaluated by determining the sensitivity of project economics to changes in baseline economic variables.